2016
DOI: 10.1016/j.ajog.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted vs traditional laparoscopic surgery for endometrial cancer: a randomized controlled trial

Abstract: In patients with endometrial cancer, robotic-assisted laparoscopic surgery was faster to perform than traditional laparoscopy. Also total time spent in the operation room was shorter in the robotic surgery group and all conversions to laparotomy occurred in the traditional laparoscopy group. Otherwise, the surgical outcome was similar between the groups. Robotic surgery offers an effective and safe alternative in the surgical treatment of endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(85 citation statements)
references
References 28 publications
2
76
2
5
Order By: Relevance
“…3 In this regard, it should be interesting to see whether both surgical approaches are similar or not when well-trained surgeons, either in conventional laparoscopy or robotic surgery, perform the same complex procedures. To date, only 1 small randomized controlled trials has been performed in women with endometrial cancer, and it compared 49 women treated by conventional laparoscopy 20 The implementation of MIS for patients with gynecological cancer may vary according to the availability of robotic technology as well as surgeon expertise. In some institutions, the introduction of robotic-assisted laparoscopy allowed to expand the application of MIS in patients with gynecological cancer, 52Y54 even in cases of obese patients, because of a shorter learning curve.…”
Section: Discussionmentioning
confidence: 99%
“…3 In this regard, it should be interesting to see whether both surgical approaches are similar or not when well-trained surgeons, either in conventional laparoscopy or robotic surgery, perform the same complex procedures. To date, only 1 small randomized controlled trials has been performed in women with endometrial cancer, and it compared 49 women treated by conventional laparoscopy 20 The implementation of MIS for patients with gynecological cancer may vary according to the availability of robotic technology as well as surgeon expertise. In some institutions, the introduction of robotic-assisted laparoscopy allowed to expand the application of MIS in patients with gynecological cancer, 52Y54 even in cases of obese patients, because of a shorter learning curve.…”
Section: Discussionmentioning
confidence: 99%
“…The details of the study population, randomization procedure, and operations have been described in detail previously. 4 The operations were performed at a tertiary referral center, the Department of Obstetrics and Gynecology of Tampere University Hospital, Tampere, Finland from 2010 to 2013 by gynecologic oncologists with several years of experience with laparoscopic surgery. The study protocol was approved by the Research Ethics Committee of Tampere University Hospital (identification code ETL R10081) and is registered at www.clinicaltrials.gov (NCT 01466777).…”
Section: Methodsmentioning
confidence: 99%
“…Because of swelling in lower extremities, many patients underwent a Doppler ultrasound imaging to exclude deep venous thrombosis with no findings. 4 Public health care in Finland uses an internal accounting and billing system within the hospitals. Different hospital units offer services based on their expertise such as anesthetic services, operating room (OR) services, laboratory services, and consultations provided by other specialties like urologic surgery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Robotic surgery achieved equivalent or better oncological results compared to laparoscopy. A Finnish investigation of 99 patients revealed no difference in the number of resected lymph nodes; but robotic surgery was associated with shorter operating times, fewer conversions to laparotomy, as well as fewer minor and major complications (31). In an American study, the robotassisted approach was found to be superior to the laparoscopic approach (32).…”
Section: Application In Malignant Gynecological Diseasementioning
confidence: 99%